2021
DOI: 10.1073/pnas.2025188118
|View full text |Cite
|
Sign up to set email alerts
|

An ecophysiological explanation for manganese enrichment in rock varnish

Abstract: Desert varnish is a dark rock coating that forms in arid environments worldwide. It is highly and selectively enriched in manganese, the mechanism for which has been a long-standing geological mystery. We collected varnish samples from diverse sites across the western United States, examined them in petrographic thin section using microscale chemical imaging techniques, and investigated the associated microbial communities using 16S amplicon and shotgun metagenomic DNA sequencing. Our analyses described a mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 95 publications
1
23
0
Order By: Relevance
“…The repetitive spikes in spectral intensity observed for all elements except Si and H along the depth profile in Figure 10 f–h are suggestive of a repetitive compositional variation through the varnish layer that could be interpreted to reflect multiple depositional cycles. The coherent behavior of Si and H suggests that silica plays an important and independent role in the development of rock varnish through the slow dissolution of silica in the presence of moisture from surficial material accumulations and then its subsequent gelling, condensation, and case hardening to form the indurated varnish layer [ 23 , 41 ] that incorporates the Mn-rich domains generated by cyanobacterial concentration [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The repetitive spikes in spectral intensity observed for all elements except Si and H along the depth profile in Figure 10 f–h are suggestive of a repetitive compositional variation through the varnish layer that could be interpreted to reflect multiple depositional cycles. The coherent behavior of Si and H suggests that silica plays an important and independent role in the development of rock varnish through the slow dissolution of silica in the presence of moisture from surficial material accumulations and then its subsequent gelling, condensation, and case hardening to form the indurated varnish layer [ 23 , 41 ] that incorporates the Mn-rich domains generated by cyanobacterial concentration [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Biological mediation by chemolithotrophic bacteria that precipitate Mn from a solution by oxidizing Mn 2+ and Mn 3+ to Mn 4+ may play a role in Mn fixation and concentration [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ], but some have argued that Mn enrichment in rock varnish is largely an abiotic inorganic process involving leaching, mobilization and photochemical oxidation [ 8 , 12 , 14 , 15 , 35 ] and that silicic acid acts as a mechanism for elemental mobilization, complexation and cementation [ 41 ]. Recently, Lingappa et al [ 16 ] described a unifying ecophysical model for rock varnish formation. Their model explains rock varnish as an aerobic microbial ecosystem governed by sunlight, water and manganese redox cycling operating in the moist environment of microdepressions on rock surfaces where dust accumulates, and photosynthetic cyanobacteria sequester high concentrations of Mn in their cells and exploit the unique redox chemistry of manganese complexes as a catalytic antioxidant system.…”
Section: Chemical Analysis Of Rock Varnishmentioning
confidence: 99%
See 1 more Smart Citation
“…Examination of the black varnish in the petrographic thin sections revealed a clear micron-size laminated pattern (Figure 7a) with a curved shape and oriented parallel to the surface. This micro texture is defined as a stromatolite structure and is typical of desert varnish [17,19,27]. Mappings of the elemental composition of the black crust revealed that Mn and Fe are not homogeneously distributed, but their content varies in the different layers of the coating.…”
Section: Scanning Electron Microscopy Coupled With Edx Microanalysis ...mentioning
confidence: 99%
“…Despite the fact that geochemical aspects of rock varnish have been thoroughly investigated [19][20][21][22][23][24] and it is believed that its primary source of material is airborne dust, there is an ongoing debate about the exact process of formation and specifically whether or not microorganisms are involved in this process [5,25,26]. In a recent study, Lingappa et al [27] proposed a new hypothesis for varnish formation. They state that Cyanobacteria accumulate manganese as a nonenzymatic antioxidant system and that, consequently to the cells death, the manganese-rich residue left behind is oxidized to generate the manganese oxides present in the varnish.…”
Section: Introductionmentioning
confidence: 99%